SISTEM REKOMENDASI CONTOH MENU MAKANAN BERAT BADAN IDEAL BERBASIS ANDROID - Yandi Aprilian Najoan; Syaiful Rahman; Izmy Alwiah Musdar (STMIK KHARISMA Makassar, 2018)
This research aim to build and implement the Foods Menu Recommendation System into android platform. This application is built using the android studio 2.0 and SQLite database. Recommendation system is a software that means to help the user by giving a recommendation to them when user face the problem to take a decision, as example what book to read, what music to listen, etc. this system have a function to give a food menu recommendation which build by some formula to count the Body Mass Index (BMI), Body Metabolic Rate (BMR), Ideal Weight, and caloric needs by using the users data weight, height, age, gender, and physical activity. From the users caloric needs, system will get some food menus from SQLite database which the total amount of the caloric needs of the food menu reach almost the same with the users caloric needs.